Pulsatile Flow of Copper Suspended Nanofluid Venture Through a Bifurcated Artery - Rao, Gade Madhava; Srinivasacharya, D.; Sreenath, I.; Bhagavan, V. S. (Communications in Mathematics and Applications, 2021)
With an aim to investigate the pulsatile flow of blood through a bifurcated artery with mild stenosis in the parent lumen in the manifestation of heat transmission. The blood is treated to be copper suspended nanofluid. The arteries forming bifurcation are assumed to be symmetric about the axis of the parent artery and straight circular cylinders of limited length. The highly nonlinear momentum and energy equations of nanofluid model are simplified by considering the mild stenosis case and a radial coordinate transformation is initiated to map irregular geometry into a rectangular grid. The solution for flow rate, impedance, shear stress are found by using the finite difference scheme in a cylindrical coordinate system. An extensive quantitative analysis has been performed based on numerical computations in order to estimate the effects of pertinent parameters on various physical quantities near the apex by means of their graphical representations so as to validate the applicability of the proposed mathematical model.
Keywords: Pulsatele blood flow; Copper nanoparticles; Bifurcated artery; Heat source parameter